Strategies to increase the stability of intermediate moisture foods towards Zygosaccharomyces rouxii: The effect of temperature, ethanol, pH and water activity, with or without the influence of organic acids. (February 2015) - Vermeulen, A.; Marvig, C.L.; Daelman, J.; Xhaferi, R.; Nielsen, D.S.; Devlieghere, F.
Abstract: Intermediate moisture foods (IMF) are in general microbiologically stable products. However, due to health concerns consumer demands are increasingly forcing producers to lower the fat, sugar and preservatives content, which impede the stability of the IMF products. One of the strategies to counteract these problems is the storage of IMF products at lower temperatures. Thorough knowledge on growth/no growth boundaries of Zygosaccharomyces rouxii in IMF products, also at different storage temperatures is an important tool for ensuring microbiologically stability. In this study, growth/no growth models for Z. rouxii, developed byVermeulen et al. (2012) were further extended by incorporating the factor temperature. Three different data sets were build: ( i ) without organic acids, ( ii ) with acetic acid (10, 000 ppm on product basis) and ( iii ) with sorbic acid (1500 ppm on product basis). For each of these data sets three different growth/no growth models were developed after 30, 60 and 90 days. The results show that the influence of temperature is only significant in the lower temperature range (8–15 °C). Also, the effect of pH is negligible (pH 5.0–6.2) unless organic acids are present. More specific, acetic acid had only an additive effect to ethanol and a w at low pH, whereas sorbic acid had also an additive effect at the higher pH values. For incubation periods longer than 30 days the growth/no growth boundary remained stable but enlarged gradually between day 60 and 90, except for the lower temperature range (<12 °C) where the boundary shifts to more stringent environmental conditions. Highlights: Lowering the temperature to refrigerated conditions improved the microbial stability substantially in media mimicking IMF. The model showed a clear effect of adding organic acid (acetic acid or sorbic acid) on the growth of Zygosaccharomyces rouxii . Model validation was performed by comparing the new data set with previous models from literature.